Physical development of 10-year students from basic school no. 10 in Torun - Gorczyński, Marcin; Napierała, Marek; Eksterowicz, Jerzy; Zukow, Walery (Journal of Education, Health and Sport, 2018)
INTRODUCTION. In order to ensure proper functioning and functioning of the organism from an early age, the child should be encouraged to exercise positive habits of physical activity. It is important to continuously monitor the somatic and motor development of young people so that they can take timely action to improve the situation. PURPOSE. The aim of the study was to investigate the level of motor and somatic features as well as sexual dimorphism of pupils from Primary School No.10 in Toruń. MATERIALS AND METHODS. The study involved 60 students (30 boys, 30 girls) aged 10 from Primary School No.10 in Toruń. Body height and body weight were measured using somatic features, body slimness, and BMI. For the measurement of motor abilities, the International Physical Fitness Test was used. Statistical tests used the Student’s t test for independent tests. Levene’s test was used to determine equality of variance. For all analyzes, the maximum permissible error I of type α = 0.05; Statistically significant p <0.05. Statistical analysis was performed in IBM SPSS Statistics 24. FINDINGS. - students from Primary School No.10 in Toruń have higher somatic characteristics than their peers from regional studies - among the studied group is the type of leptosomal structure - almost all students have a normal body weight and fall into the normal range CONCLUSION. Girls and boys from Primary School No.10 in Toruń are physically more fit than their colleagues in regional studies.